Synthesis and self-assembly of benzothiadiazole-cored α-cyanostilbene hexacatenar mesogens. Issue 4 (1st October 2020) - Xiao, Yulong; Liu, Xiaotong; He, Qingyao; He, Xin; Zhang, Dongxian
ABSTRACT: A novel series of biscyanovinyl diphenylbenzothiadiazole-based polycatenars with 3, 4, 5-trialkoxyl benzene units at both ends were synthesized in high yield. The terminal alkyl chain length had great effect on the self-assembly properties. Upon terminal alkyl chain elongation, these compounds showed a mesophase transition from Colrec / p 2 mm phase to Colhex/p6 mm phase in their bulk states and could aggregate into organogels with complex morphologies varying from 2D nanosheets via partial spheres to absolute 3D spherical flower-like morphologies. The results indicated that changing the alkyl chain length could tune supramolecular assembly nanostructures of the polycatenars effectively.